Damaging effect of ischemia on the development of retinal organoids derived from human embryonic stem cells - Yu-Han Yan; Hong-Yu Li; Li-Xiong Gao; Wen Li; Ling-Ping Zhao; Quan Zeng; Yu Luo; Tian-Tian Cui; Ru-Ge Zang; Zi Ye; Jia-Fei Xi; Wen Yue; et al. (International Journal of Ophthalmology, 2025)
AIM: To explore the changes in early retinal development after the occurrence of ischemia. METHODS: Human retinal organoids (hROs) of day 18 or day 30 were treated with oxygen-glucose deprivation and reperfusion (OGD/R) to simulate the retinal ischemia. All hROs were maintained normally until day 60 to evaluate changes in ischemic injuries during retinal development. Paraffin section staining was used for detecting changes in organoid structure and cell number. Real-time quantitative polymerase chain reaction (RT-qPCR) and Western blot (WB) analyses were used to observe the change in the expression of retinal cell markers. RESULTS: In hROs, OGD/R induced the decrease of proliferating cells, inhibited the expression of proliferated marker Ki67 and promoted early apoptosis of retinal cells (P<0.05). Under OGD/R condition, the progenitor cell layer and ganglion cell layer of hROs lost normal structure, and the number of neural stem cells (SOX2+), retinal progenitor cells (CHX10+) and retinal ganglion cells (TUJ1+/BRN3+/ATOH7+) decreased (P<0.05). The expression of corresponding retinal cell markers also decreased (P<0.05). Organoids treated with OGD/R on day 30 had similar injuries in retinal structure and retinal cell markers to those on day 18. Long-term observations revealed that day 18-treated organoids remained disorganized progenitor and ganglion cell layers by day 60, with no recovery in proliferating cell nuclear antigen (PCNA) protein expression. RT-qPCR showed persistently low Ki67 transcription levels (P<0.001), while other retinal cell markers recovered or exceeded normal levels, indicating a limited self-repair happened in the development of hROs. In contrast, day 30-treated organoids exhibited normal structure and marker expression by day 60, with transcription levels of retinal cell markers returning to normal (P>0.05), demonstrating complete recovery from OGD/R damage. CONCLUSION: Retinal ischemia damage the retinal development in the short-term. After the restoration of retinal blood supply, the retinal ischemic damage can be recovered during subsequent development. However, retinal ischemic injuries at different developmental stages exhibit varying degrees of reversibility. The earlier ischemic injury occurs, the more difficult it is to repair retinal cell and structure damage.